Hermeneutika al-Qur’an “Mazhab Yogya” Telaah atas Teori Ma’nā-cum-Maghzā dalam Penafsiran al-Qur’an - Asep Setiawan (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2016)
This article tries to discuss the discourse of the necessity of the application of the hermeneutic method in Qur’anic studies with the theory of interpretation ma’nā-cum-maghzā offered by Muslim scholars in Yogyakarta. In conclusion, the efforts of the initiators of the hermeneutic of the Qur’an to make hermeneutics be one approach and partners in the study of the Qur’an is an effort that needs to be appreciated, and the goal is to develop Islamic Studies (particularly the study of the Quran). The interpretation of the Qur’an with the theory ma’nā-cum-maghzā , is a method of interpretation of the results of elaboration. If this theory is applied in the interpretation of the Qur’an, it will produce a relative interpretation, or tentative interpretation, and dynamic one that always demands a change in accordance with the age, social and cultural backgrounds. Its implication is no final interpretation. So, Muslims will not ever understand absolutely the truth of the content in Qur’an, because it is dynamic and constantly changing. However, taking into account the assumptions and implications, hermeneutics is not appropriate to be applied in the study of the Qur’an. If it applied to interpret the Qur’an, then it will lead to confusions and doubts. This is because it departed from skepticism and relativism, equating the Qur’anic text as plain texts, requiring uncertainty meanings and relative-tentative interpretations.